ANALYSIS OF THE DEVELOPMENT AND VISUAL SEMIOTICS OF UHT ULTRA MILK DRINK PRODUCT PACKAGING - Fitra Al Hafidz; Rahul Anandya Prasetya; Fuji Anugrah, Aliyah (Journal Informatic, Education and Management (JIEM), 2026)
The beverage industry is one of the fastest growing industries today, therefore packaging is one of the things that a company needs to pay attention to in communicating its products. This study examines the development of packaging design for UHT Ultra Milk products since the 1970s. Ultra Milk is produced by PT Ultrajaya which has been established since 1971. Currently, PT Ultrajaya has many other products that are well known to the public in Indonesia and abroad. This study was conducted to study how the development of packaging design and visual semiotics of UHT Ultra Milk packaging adapts to the times. This study uses a descriptive qualitative method and Roland Barthes' semiotic approach as data analysis that includes three levels of reading: denotation, connotation, and myth. Throughout the journey of the Ultra Milk product, there have been several changes in packaging design, but some visual elements are maintained and become the characteristics of a product. The results of the study show the importance of consistent visual elements in forming a product identity. This research is expected to contribute to industry players in communicating their products.